Transition To A Green Economy In The Context Of Selected European And Global Requirements For Sustainable Development; Przejsćie do zielonej gospodarki - w konteksćie wymogoẃ europejskich i globalnych ukierunkowanych na zroẃnowazȯny rozwoj́ - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2013)
The aim of the paper is to present selected aspects of sustainable development related to environmental protection and the creation of a green economy, with special reference to the global and European context for the development of an environmentally friendly goods and services market, taking into account the cases of Central and Eastern European countries. One of the most important elements of the strategy to promote clean economic growth and foster the transition to a more sustainable and greener economy is the energy sector, where the aim is to reduce greenhouse gas emissions and sulfur oxides and support the development of renewable energy sources. Some of the achieved results in this area are presented in this paper. – – Celem artykułu jest przedstawienie wybranych aspektoẃ zroẃnowazȯnego rozwoju w odniesieniu do ochrony sŕodowiska i budowy "zielonej gospodarki" w konteksćie uwarunkowanǵlobalnych i europejskich dla rozwoju rynku towaroẃ i usług sŕodowiskowych (szczegoĺna uwage posẃiecono w nim krajom Europy Sŕodkowej i Wschodniej). Jednym z najbardziej istotnych aspektoẃ jest roẃniezṗromowanie czystego wzrostu ekonomicznego w celu wzmocnienia przechodzenia do bardziej zroẃnowazȯnej i bardziej zielonej gospodarki w sektorze energetycznym, przez wdrazȧnie redukcji emisji gazoẃ cieplarnianych i tlenkoẃ siarki oraz przez rozwoj́ energetyki bazujacej na odnawialnych nosńikach energii. Pewne osiagniecia w tej dziedzinie zostały zaprezentowane w niniejszym artykule.
Keywords: 330; sustainable development; environmentally friendly goods and services; green economy; energy policy